The effect of anticipated achievement feedback on students' semantic processing as indicated by the N400 cloze effect. (February 2017) - Janssen, Eva M.; van der Ven, Sanne H.G.; van Hoogmoed, Anne H.; Leseman, Paul P.M.
Abstract: The present study examined the effects of anticipated achievement feedback on students' semantic processing on the neural level, using event-related brain potentials (ERPs). Participants ( N  = 79) anticipated either self-referential or normative achievement feedback regarding an announced upcoming test. Additionally, their performance expectations (low vs. no expectations) were orthogonally manipulated. Subsequently, students' on-line semantic processing was assessed by measuring the N400 cloze effect, a component in the EEG signal of which the amplitude is associated with semantic processing. Within the low performance-expectation condition, no effect of anticipated feedback on semantic processing was found. Within the no-performance-expectation condition, participants anticipating self-referential feedback showed a more widely distributed N400 cloze effect than participants anticipating normative feedback. The results confirmed the hypothesis that the mere expectation of a particular type of feedback can affect students' semantic processes. Highlights: Using ERPs (N400), we investigated effects on efficiency of semantic processing of 1. anticipating self-referential vs. normative feedback (A-SR-F vs. A-N-F), and 2. having no or low expectations of performance on a future test. As suggested by differences in the distribution of the N400 effect over the scalp, A-SR-F led to more efficient semantic processing than A-N-F in the no-expectation group.